Cosmological Perturbations via Quantum Corrections in M-Theory - Kazuho Hiraga (MDPI AG, 2021)
In the early universe, it is important to take into account the quantum effect of gravity to explain the feature of inflation. In this paper, we consider the M-theory effective action which consists of 11-dimensional supergravity and (Weyl)<semantics>4</semantics> terms. The equations of motion are solved perturbatively, and the solution describes the inflation-like expansion in 4-dimensional spacetime. Equations of motion for tensor perturbations around this background are derived perturbatively. We also check that the equations of motion are obtained from the effective action up to the second order of the perturbations. Finally, we solve the equations of motion for the tensor perturbations perturbatively and obtain analytic expressions for them.